Weaving Words, Making Bridges: a Linguistic Mediation Experience in Tseltal-Spanish (2024)
The article shows a reading-writing intervention experience with monolingual students in Tseltal, inhabitants of the municipality of Yajalón in the state of Chiapas. The purpose of this experience was to implement Tseltal-Spanish linguistic mediation as a pedagogical strategy for teaching second languages in a context of cultural and linguistic diversity. From a participatory action research methodology (PAR), based on microethnographic observation, semi-structured interviews and the collaborative design of didactic sequences, it is provided a landscape about problems concerned to Spanish language learning in a group of 21 students between six and seven years old. The results reflect: 1) The benefits of PAR when students are considered agents of their own knowledge and 2) The improvement in Spanish learning, reflected in a school environment of increasing confidence with the support of a mediating agent which promotes the learning based on “the Tseltal word”. Thus, it is concluded that Tseltal (L1) represents not just a communicative channel, but a pedagogical implement for the Spanish learning (L2), that is like a foreign language in this context, alien to the reality of the linguistic community in question.